The method and resources of the Indigo in his book The Select from the People of the Sultan, the Released People of Faith - Hammed, Ahmed Abdullah (Al-Adab Journal, 2022)
Methodological studies open up broad horizons towards identifying the contents of books in general, and our book in question is considered a historical story book from reality, and this trend has been widely known in historical notation, and we shed light on the life of the work, and it is considered one of the flags of the front school doctrine as this is highlighted through the works that he authored and then a systematic study The resources and his style in the book is a group of news that tells the stories of a number of those who had the honor to meet Imam Mahdi in the great backbiting that they had miracles that resulted in the healing of the sick or the elimination of a need that was presented in random order. Al-Ma'ajir and what our role in it was to study the author’s life in all its aspects and to study his methodology in the presentation and to push the suspicion of the book to the authorship in this aspect and to refer to the sources that transmitted that news before him and those who adopted it after him from among the leaders of the compilers and to meet those texts transmitted by others and a brief clarification of each story